2008
DOI: 10.2478/10004-1254-59-2008-1894
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mineral Cationic Carrier Against Sulphur Mustard in Skin Decontamination

Abstract: Efficacy of Mineral Cationic Carrier Against Sulphur Mustard in Skin DecontaminationThe aim of this study was to evaluate decontamination (absorption) efficacy of a preparation called Mineral Cationic Carrier (MCC®) against skin contamination with sulphur mustardin vivo. MCC® is a synthetic preparation with known ion exchange, absorption efficiency, and bioactive potential. CBA mice were applied increasing doses of sulphur mustard on their skin and MCC® was administered immediately after skin contamination. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
1
Order By: Relevance
“…Sulfur mustard (SM) or bis (chloroethyl) sulfide with a molecular formula of C 4 H 8 Cl 2 S is a toxic chemical agent that belongs to a class of vesicant compounds [ 1 , 2 ]. César-Mansuète Despretz and Alfred Riche reported SM synthesis from the ethylene and sulfur dioxide reaction in 1822 and 1854 [ 3 ].…”
Section: A Brief History Of Sulfur Mustardmentioning
confidence: 99%
“…Sulfur mustard (SM) or bis (chloroethyl) sulfide with a molecular formula of C 4 H 8 Cl 2 S is a toxic chemical agent that belongs to a class of vesicant compounds [ 1 , 2 ]. César-Mansuète Despretz and Alfred Riche reported SM synthesis from the ethylene and sulfur dioxide reaction in 1822 and 1854 [ 3 ].…”
Section: A Brief History Of Sulfur Mustardmentioning
confidence: 99%
“…Nadalje, oni sporije djeluju i imaju veću LD 50 od živčanih (9,14,23,70). Njihova je dekontaminacija velik izazov za znanstvenike koji se bave proučavanjem tih kemijskih reakcija, jer su to jako agresivne kemikalije (76,77).…”
Section: Biološke Nokseunclassified
“…Our earlier study on CBA has shown that it is also an effi cacious skin decontaminant against high doses of sulphur mustard (13). This study was performed on a similar in vivo model (NOD mice) to evaluate the effi cacy of MCC ® against chemical warfare agent sarin.…”
Section: MCCmentioning
confidence: 99%
“…Preclinical toxicology testing performed according to the standards and regulations of the Organization for Economic Cooperation and Development (OECD) did not indicate acute, sub-chronic, or chronic toxicity of the preparation (11), and it proved effi cacious against skin contamination with warfare nerve agent sulphur mustard (13). In this study, we investigated the effi cacy of MCC ® against skin contamination with sarin.…”
mentioning
confidence: 99%